2022
DOI: 10.1371/journal.pone.0266599
|View full text |Cite
|
Sign up to set email alerts
|

Device-worn measures of sedentary time and physical activity in South Asian adults at high risk for type 2 diabetes in Metro-Vancouver, Canada

Abstract: Background South Asians have high incidence of chronic disease. Physical activity (PA) and sedentary time are modifiable risk factors for chronic disease but their assessment in South Asians has been primarily based on self-report. This study presents directly-measured PA and sedentary time in South Asian adults in Canada. Methods A subset of 100 South Asian participants from a larger study who were identified at being at a higher risk for type 2 diabetes wore Actical accelerometers for 7 days. Anthropometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Although existing studies have shown that physical activity (PA) can reduce the risk of UFs,5 6 sedentary time is now recognised as not only as the absence of PA but also as a distinct set of behaviours. The health implications of sedentary behaviour are distinct from those related to a lack of exercise 15 16. Sedentary behaviour damages the metabolism and increases the risk of all-cause death.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although existing studies have shown that physical activity (PA) can reduce the risk of UFs,5 6 sedentary time is now recognised as not only as the absence of PA but also as a distinct set of behaviours. The health implications of sedentary behaviour are distinct from those related to a lack of exercise 15 16. Sedentary behaviour damages the metabolism and increases the risk of all-cause death.…”
Section: Introductionmentioning
confidence: 99%
“…The health implications of sedentary behaviour are distinct from those related to a lack of exercise. 15 16 Sedentary behaviour damages the metabolism and increases the risk of all-cause death. At the same time, sedentary behaviour is also associated with oestrogen-dependent tumours, such as endometrial cancer, 17 ovarian cancer 18 19 and breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However, some limitations apply related to inadequate representation of the sub-groups within the South Asian diaspora and thus findings need to be interpreted with caution as they cannot be applied to all South Asians. Also, as we were not able to touch upon sedentary time, and its conceptualization among the South Asian community, we recommend that future studies explore this phenomenon adequately especially considering the relatively high sedentary time accumulated by the participants in our accelerometer-based study [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of steps per day Steps (n/day) was used to analyze the level of physical activity related to commuting in: Sedentary (<5000 steps/day); Little active (5000 -7499 steps/day); Insufficient active (7500 -9999 steps per day); Active (10000 -12500 steps/day); Very active (> 12500 steps/day) (MAHMOOD; NETTLEFOLD; ASHE; PUYAT et al, 2022).…”
Section: Study Variablesmentioning
confidence: 99%